2012
DOI: 10.1016/j.aquaculture.2011.11.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature and pH on the growth and physiological response of juvenile yellowtail kingfish Seriola lalandi in recirculating aquaculture systems

Abstract: ÔØ Å ÒÙ× Ö ÔØPlease cite this article as: Abbink, Wout, Blanco Garcia, Ainhoa, Roques, Jonathan A.C., Partridge, Gavin J., Kloet, Kees, Schneider, Oliver, The effect of temperature and pH on the growth and physiological response of juvenile yellowtail kingfish Seriola lalandi in recirculating aquaculture systems, Aquaculture (2011), doi: 10.1016/j.aquaculture.2011.11.043 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(89 citation statements)
references
References 40 publications
9
68
2
1
Order By: Relevance
“…It is probable that more CO 2 has been released due to a greater bacteria activity in BF and BP tanks (Azim, Little, & Bron, 2008). BF and BP tanks require a stricter monitoring to avoid acidosis caused by CO 2 (Abbink et al, 2011). Dissolved oxygen (DO 2 ) did not differ among treatments (p > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…It is probable that more CO 2 has been released due to a greater bacteria activity in BF and BP tanks (Azim, Little, & Bron, 2008). BF and BP tanks require a stricter monitoring to avoid acidosis caused by CO 2 (Abbink et al, 2011). Dissolved oxygen (DO 2 ) did not differ among treatments (p > 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…Similar results were found by 49 who stated that the favorable temperature of the Clarias is between 25 -30 ℃, he also reported that fish would grow faster with the increase in temperature to a certain level, then growth will reduce with further rises in temperature. The poor growth performance at a temperature higher than the optimum was also reported for Japanese yellowtail by 47 as a result of a significant decrease in food intake coupled with an increased demand for energy at such higher temperatures.…”
Section: Blood Parametersmentioning
confidence: 87%
“…The results revealed that fishmeal-based protein with TemperatureT2(28℃) gave the higher count of (MCV) while peameal-based diet gave the lowest number of (MCV) for C. gariepinus. Effect of temperature on fish growth 47 stated that the key (abiotic) factor that affecting fish growth is water temperature. In this study, the growth rate of C. gariepinus was significantly higher at the temperature of 28℃ as reported by 48 .The temperature of 28 ℃, was found to be optimum for the growth of C. gariepinus while the lowest growth performance was shown at temperature 30℃.…”
Section: Blood Parametersmentioning
confidence: 99%
“…The lowest concentrations of free CO 2 in water were observed in the nocturnal + diurnal aerated tanks, which differed significantly from the nonaerated tanks (p < 0.05; Table 1). The nocturnal aeration of water is prone to remove significant amounts of CO 2 from the water because the highest levels of CO 2 occur overnight (Abbink et al, 2012).…”
Section: Resultsmentioning
confidence: 99%